Analysis of environmental sanitation indicators for the central west region of Espírito Santo/BR - Elias, Caroline Jaques; Feroni, Rita de Cassia (Brazilian Journal of Production Engineering, 2023)
The guarantee of availability and sustainable management of water is a human right, however, there are numerous challenges to effectively achieve basic sanitation in a region. In this context, the present study aimed to analyze environmental sanitation indicators for the west central region of the state of Espírito Santo-BR, from 2010 to 2021, encompassing 8 cities, based on 7 indicators collected from the National Sanitation Information System (SNIS) totaling 168 data. The indicators collected from the SNIS were compared against the goals and reference data established for the years 2010, 2017 and 2023. As main results, the indicators of incidence of non-standard total coliform analyzes and average per capita water consumption stand out as satisfactory and unsatisfactory extremes, respectively, for the study region in all years of analysis. With the intention of monitoring, the study can be a source of assistance to managers in the preparation of plans that promote the improvement of environmental sanitation indicators, it is emphasized the importance of sending assiduous and reliable information on the indicators by the sanitation service providers to the SNIS, since the absence of information in some municipalities made a more detailed analysis impossible.
Keywords: Water Resources Management; Environmental Sanitation Indicators; Sustainability